Protocol: Pentoxifylline optimal dose finding trial in preterm neonates with suspected late onset sepsis (PTX-trial) - Serife Kurul; H. Rob Taal; Robert B. Flint; Jan Mazela; Irwin K. M. Reiss; Karel Allegaert; Sinno H. P. Simons (BMC, 2021)
Abstract Background Late onset sepsis is a leading cause of death and morbidity in preterm infants. Despite optimal antibiotic treatment, sepsis related mortality and morbidity is still high. Pentoxifylline (PTX) is a methylxanthine with promising immunomodulatory properties, which can be used as an additional therapy next to antibiotics in preterm infants. PTX is increasingly used off-label in neonatal intensive care units, however up till now no dose finding study has been done for PTX in this specific population. The aim of this study (PTX-trial) is to determine the optimal dose of PTX in preterm infants (gestational age < 30 weeks) with (suspected) late onset sepsis. Dose finding in this particular population is unique, since for most drugs used in neonates the optimal dosage has not been investigated in phase II dose-seeking studies. Methods The PTX-trial is a prospective open label sequential dose-optimization study with an adapted continual reassessment method. An up-and-down dose-response design will be used, with dose step-up and step-down titration after every 3 patients. The PTX starting dosage will be 30 mg/kg/day in 6 hours as described in most previous neonatal studies. Efficacy is defined by means of biochemical and clinical parameters. Toxicity in these vulnerable patients is unwarranted. The optimal dose is defined as the ED75 (i.e., clinically and chemically effective dose for 75% of patients) in preterm neonates with late onset sepsis. We plan to include 30 neonates to determine the optimal dose using this study design. Subsequently, the optimal dose will be validated in 10 additional preterm neonates. In parallel, pharmacokinetics of PTX and its metabolites will be described as well as longitudinal evaluation of metabolomics and proteomics. Discussion The study has been approved by the Regional Medical Ethics Board of Erasmus Medical Center University Rotterdam (MEC 2019-0477) and registered at Clinicaltrials.gov (NCT04152980). Results of the main trial and each of the secondary endpoints will be submitted for publications in peer-reviewed journals. Trial registration Clinicaltrials.gov, NCT04152980 , Registered November 6th, 2019